2010
DOI: 10.1021/nn101192z
|View full text |Cite
|
Sign up to set email alerts
|

pH-Dependent Toxicity of High Aspect Ratio ZnO Nanowires in Macrophages Due to Intracellular Dissolution

Abstract: High-aspect ratio ZnO nanowires have become one of the most promising products in the nanosciences within the past few years with a multitude of applications at the interface of optics and electronics. The interaction of zinc with cells and organisms is complex, with both deficiency and excess causing severe effects. The emerging significance of zinc for many cellular processes makes it imperative to investigate the biological safety of ZnO nanowires in order to guarantee their safe economic exploitation. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
91
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(106 citation statements)
references
References 41 publications
10
91
0
Order By: Relevance
“…[28][29][30] However, in this study, we believe that shape was not the main factor in toxicity discrepancy when comparing these two nanomaterials with low-aspect-ratio particles. Müller et al 33 attributed the toxic effects of ZnO nanowires to released zinc ions, rather than to the high aspect ratio, implying that the rapid dissolution of ZnO may have reduced the effect of the NP shape. The average size of the ZnO a NPs was 47.1±5.1 nm, with width 27.9±1.8 nm, and the average size of the ZnO b NPs was 18.5±1.2 nm, with width 6.8±0.5 nm, which was smaller than that of the ZnO a NPs.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] However, in this study, we believe that shape was not the main factor in toxicity discrepancy when comparing these two nanomaterials with low-aspect-ratio particles. Müller et al 33 attributed the toxic effects of ZnO nanowires to released zinc ions, rather than to the high aspect ratio, implying that the rapid dissolution of ZnO may have reduced the effect of the NP shape. The average size of the ZnO a NPs was 47.1±5.1 nm, with width 27.9±1.8 nm, and the average size of the ZnO b NPs was 18.5±1.2 nm, with width 6.8±0.5 nm, which was smaller than that of the ZnO a NPs.…”
Section: Discussionmentioning
confidence: 99%
“…26 Furthermore, Müller et al showed that pH-triggered intracellular release of ionic Zn 2+ is responsible for the toxicity of ZnO nanowires. 27 The toxic effects of ZnO NPs are due to their solubility, resulting in increased intracellular [Zn 2+ ]. This results in cytotoxicity, oxidative stress, and mitochondrial dysfunction.…”
Section: +mentioning
confidence: 99%
“…ZnO nanowires were taken up by macrophages through phagocytosis and dissolved in lysosomes. 27 Again, the effects of ZnO NPs are likely caused by Zn 2+ .…”
Section: In Vitro Studies Using Cells Of the Immune Systemmentioning
confidence: 99%
“…ZnO NPs exhibit protein adsorption property which might be responsible for their cytotoxicity [142]. The pH-triggered (acidic) intracellular release of Zn 2+ is mainly responsible for the toxicity of ZnO nanowires [143].…”
Section: Safety Concerns With Zno Npsmentioning
confidence: 99%